2005
DOI: 10.1017/s1474746404002209
|View full text |Cite
|
Sign up to set email alerts
|

The Development of Direct Payments in the UK: Implications for Social Justice

Abstract: Direct payments have been heralded by the disability movement as an important means to achieving independent living and hence greater social justice for disabled people through enhanced recognition as well as financial redistribution. Drawing on data from the ESRC funded project Disabled People and Direct Payments: A UK Comparative Perspective, this paper presents an analysis of policy and official statistics on use of direct payments across the UK. It is argued that the potential of direct payments has only p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
57
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 5 publications
1
57
0
Order By: Relevance
“…Information exchange, system organisation inflexibilities, concomitant 'excessive bureaucracy' and a lack of management leadership are portrayed as keys to understanding 'poor performance' (Commission for Social Care Inspection, 2004a). Other commentators have tended to emphasise wider resource constraints, process complexities, local party political traditions, surfeits of social movement activism and conflicts between the interests of workers, carers and users as the central disabling factors (Glendinning et al, 2000a;Barnes et al, 2004;Spandler, 2004;Riddell et al, 2005).…”
Section: Policy Backgroundmentioning
confidence: 99%
“…Information exchange, system organisation inflexibilities, concomitant 'excessive bureaucracy' and a lack of management leadership are portrayed as keys to understanding 'poor performance' (Commission for Social Care Inspection, 2004a). Other commentators have tended to emphasise wider resource constraints, process complexities, local party political traditions, surfeits of social movement activism and conflicts between the interests of workers, carers and users as the central disabling factors (Glendinning et al, 2000a;Barnes et al, 2004;Spandler, 2004;Riddell et al, 2005).…”
Section: Policy Backgroundmentioning
confidence: 99%
“…The National Personal Budget survey found that the 'single most commonly commented upon issue in the survey was a lack of clarity, often regarding how money could or couldn't be used, but also concerning other aspects of personal budgets as well' (Hatton and Waters 2011: 19). Inequalities in the capacity of citizens to navigate complex care systems have been a concern raised by many people, particularly in the context of personal budgets (Riddell et al 2005;Barnes 2008;Glendinning 2008;Slasberg and Hatton 2011). Advocates of personalisation argue that the care systems that predated personal budgets were themselves characterised by complexity, lack of transparency and inequity.…”
Section: A Matter Of Rightmentioning
confidence: 99%
“…Specifically, Pedlar and her colleagues found that privatization and the emergence of for-profit service providers forced all agencies within the sector to maximize revenues and lower costs. The disabilities studies literature has also considered the implications of government restructuring on direct support workers and acknowledged conflicting social justice frames between disability advocates and union activists (Riddell et al, 2005).…”
Section: End-users As Industrial Relations Actorsmentioning
confidence: 99%